Strategic Management: TNI Manunggal Builds Villages as Bhakti TNI - Johnson Kennedy, Posma Sariguna (Universitas Kristen Indonesia, 2022)
In operations other than war, it is stated that the TNI also has to assist regional governments. Together with the local government, the TNI has collaborated to carry out development in various fields jointly. The TNI has a Bhakti TNI program, namely TNI Manunggal Building Villages (TMMD), as the involvement of the TNI as a state tool to support the development and implementation of regional government without neglecting vigilance and National Defense and Security. This paper aims to look at the strategic management of the TMMD program. The research method used is a descriptive qualitative literature study. It will review it from the rationale SWOT analysis (strengths, weaknesses, opportunities, and threats) to strategic policies and evaluations from the TNI Manunggal Village Development implementation.Keywords: TNI, Unity, Village Building, Strategic Management